MANAJEMEN KELAS BERBASIS INTERVENSI DENGAN PENDEKATAN KOGNITIF PADA PEMBELAJARAN BAHASA INDONESIA - Erika Nova Rahman (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2019)
This research is culaitative field research, the subject of this study is the students and teachers of Roudlotul Ulum Islamic High School Dinoyo Jatirejo Mojokerto. The purpose of this study is to describe the problems of classroom management and the implementation of intervention-based classroom management with a cognitive approach to learning Indonesian in class XI Islamic High School Roudlotul Ulum Dinoyo. The results of this study are found three sources of management problems that are sourced from the teacher, emotional students and non-formal actions. The implementation has three stages, planning, implementation and supervision where the implementation has fulfilled the characteristics of effective interventions participation, consistency and follow-up, dexterity, clarity, follow-up, and finally, ethics of attitude. Keywords: Implementation, Intervention Based Classroom Management, Cognitive Approach.